1998
DOI: 10.1021/la980542i
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Molecular Shape and the Orientational Distribution in the Langmuir−Blodgett Film of a Bent-Shaped Achiral Molecule As Studied by Surface Second-Harmonic Generation

Abstract: We have studied the anisotropic molecular orientational distributions of two-dimensional bent-shaped molecular monolayers by optical surface second-harmonic generation (SHG). The molecular monolayer of 1,3-phenylene bis[4-(((4-dodecylphenyl)imino)methyl)benzoate] (12-PIMB) was prepared by the Langmuir−Blodgett (LB) technique. Oblique incident surface SHG measurements from the monolayer showed that the bent-shaped molecules preferably aligned toward the dipping direction. The analysis of the experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 41 publications
2
31
2
Order By: Relevance
“…Thus, according to the MakerFringes method, angle dependent SHG-measurements were performed for mono-and multilayer LB-structures implementing both significant P-In/P-Out and S-In/P-Out laser beam polarization geometries as explained before. The estimated NLO-coefficients are in good agreement with those reported in the literature for bent-shaped compounds composed of several benzene rings [5,18,[34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Thus, according to the MakerFringes method, angle dependent SHG-measurements were performed for mono-and multilayer LB-structures implementing both significant P-In/P-Out and S-In/P-Out laser beam polarization geometries as explained before. The estimated NLO-coefficients are in good agreement with those reported in the literature for bent-shaped compounds composed of several benzene rings [5,18,[34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…In general, the experimental data may deviate from this approach for excessive multilayer depositions, where the system may drastically turn into a mechanically unstable configuration. Up to date, only a few studies of monolayer bent-core based LB-systems have been reported in the literature [5,6,8,9,12]. Indeed, the improvement of multilayer LB-systems with the fascinating bent-core "banana" compounds seems to be a challenging task of current interest, since a collapse of an excessive number of deposited layers seems to occur for this kind of compounds, as is shown in this work.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations